Treatment Considerations for Pyoderma Gangrenosum After Reduction Mammoplasty in an Unsuspecting Patient Demographic - Natalia A. Pluta, MS; Tamara L. Kemp, MD; Shayna C Rivard, MD (Plastic and Reconstructive Surgery, Global Open)
Summary:. Pyoderma gangrenosum (PG) is a rare, often idiopathic, noninfectious inflammatory neutrophilic dermatitis that causes painful ulcerative cutaneous papillomatous lesions. PG often mimics surgical infection, wound dehiscence, and postoperative cellulitis, leading to high rates of misdiagnosis and mistreatment. Here, a healthy 17-year-old adolescent girl with congenital breast asymmetry, macromastia, and a history of only mild intermittent autoimmune conditions developed an open wound along her inferior left breast incision 2 weeks after reduction mammoplasty. With continued enlargement and development of new ulcerative lesions despite appropriate local wound care, clinical suspicion for PG was raised. Standard treatment with oral prednisolone and topical tacrolimus led to incomplete resolution, and subsequent regression on attempts to taper the corticosteroid. Transition to oral cyclosporine with continued daily topical tacrolimus ultimately led to complete healing. This case underscores the need for a high clinical suspicion for PG in nonhealing ulcerative lesions after breast surgery, in addition to the importance of timely initiation of immunomodulatory agents and modification of the regimen if incomplete resolution is encountered.